STUDI KUANTITATIF KEJADIAN HEPATITIS B PADA IBU HAMIL - Darmawaty Rauf; Sriwati Palaguna; Bayu Pratama Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Hepatitis B is a life-threatening infectious disease worldwide. Data from the WHO indicate that more than 257 million people worldwide are infected with hepatitis B, and as many as 887,000 die each year from complications of hepatitis B. The objective of this study is to determine the causes of hepatitis B among pregnant women. The study design used in this research is cross-sectional. The study was conducted in the service area of the Kalumata Community Health Center. The study was carried out in September 2025. The study population consisted of all pregnant women registered at the Kalumata Community Health Center. The study sample comprised 85 respondents. The sampling technique used was purposive sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between a history of blood transfusion (p-value: 0.043) and a history of hepatitis B vaccination (p-value: 0.032) with the occurrence of hepatitis B in pregnant women. It is recommended that healthcare workers schedule monthly home visits or scheduled seminars for pregnant women so that they can receive information regarding early prevention of hepatitis B. Furthermore, pregnant women are encouraged to always maintain their health and avoid activities that could lead to hepatitis B infection. Keywords: Hepatitis B, Pregnant Women, Blood Transfusions